Foraging activities, success and efficiency of cattle egrets (Bubulcus ibis) in three habitat types in the Greater-Accra Region of Ghana. - Kuranchie, A; Kyerematen, R; Attuquayefio, D.K; Holbech, L.H (Journal of Biological and Food Science Research, 2 (4):45-50, 2013)
Cattle egrets are considered one of the most widely distributed bird species globally. They are regarded as cosmopolitan due to their ability to adapt to different habitats and spread over anthropogenic habitats such as lawns and landfill sites. This study investigated their relative abundance, foraging success and efficiency in three habitat types (grassy areas, silted drain, and landfill sites) in the Greater Accra Region of Ghana. The number of total strikes (strike = a peck made by the bird when foraging which may or may not result in prey capture) and successful strikes (identified by a characteristic head-jerk swallowing behaviour of the birds) were used to assess foraging success and efficiency. Mean successful strike rate was significantly different across the three major habitat types (H = 10.97, p < 0.05) with cattle egrets foraging at the landfill sites recording the highest (4.79 ± 2.82 min-1) and those in the grassy areas the lowest (2.32 ± 1.54 min-1). The maximum number of successful strikes in a minute by a cattle egret was 12, 16 and 23 at the grassy, silted drain, and landfill sites respectively. Cattle egrets at the landfill sites were the most efficient (75 %) foragers. Landfill sites should be managed to control the populations of cattle egrets
Keywords: Cattle egret; foraging success; foraging efficiency; landfill site; Greater Accra